Keys to second Corinthians: revisiting the major issues - Murphy-O'Connor, J. (Oxford University Press, 2010)
A companion to 'Keys to First Corinthians', this volume is essential reading for students & scholars of Second Corinthians. It brings together 12 influential journal articles on the epistle from a leading expert in the field.